2017
DOI: 10.17221/182/2015-pps
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium-plant interaction: state of the art - a review

Abstract: Dinolfo M.I., Castañares E., Stenglein S.A. (2017): Fusarium-plant interaction: state of the art -a review. Plant Protect. Sci., 53: 61-70.One of the most important genera able to develop diseases in cereals is Fusarium which not only produces losses by the fungal presence but also mycotoxin production harmful to human and animal consumers. In the environment, plants are continuously threatened by abiotic and biotic stresses. Among the latter, pathogens gained importance mainly due to their ability to affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…For instance, Arabidopsis etr1 mutants showed less symptoms of Fusarium wilt than control plants and it also increased expressions of SA-encoding genes [121]. ET signalling is responsible for plant defence responses against fungal pathogens, for instance, ET signalling impaired Arabidopsis mutants showed higher resistance for F. graminearum; however, overexpressed mutants with ET signalling elicited Fusarium susceptibility confirming the integral role of ET in Fusarium-plant interactions [122,123]. Similarly, the etr1-1 mutant enhanced plant resistance against F. oxysporum in Arabidopsis, suggesting that ETR1 is also needed for disease development [121].…”
Section: Phytohormonal Defence Signalling Against Fusarium Pathogensmentioning
confidence: 87%
“…For instance, Arabidopsis etr1 mutants showed less symptoms of Fusarium wilt than control plants and it also increased expressions of SA-encoding genes [121]. ET signalling is responsible for plant defence responses against fungal pathogens, for instance, ET signalling impaired Arabidopsis mutants showed higher resistance for F. graminearum; however, overexpressed mutants with ET signalling elicited Fusarium susceptibility confirming the integral role of ET in Fusarium-plant interactions [122,123]. Similarly, the etr1-1 mutant enhanced plant resistance against F. oxysporum in Arabidopsis, suggesting that ETR1 is also needed for disease development [121].…”
Section: Phytohormonal Defence Signalling Against Fusarium Pathogensmentioning
confidence: 87%
“…In this study, there was high intrapopulation genetic variation for population 1 (94.63%) which consisted largely of isolates collected from North Trinidad compared to populations 2 and 3, perhaps due to larger sample size. It was reported that for Fusarium poae isolates, genetic variability was explained by differences within rather than between Argentinean and English populations (Dinolfo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Akbar et al (2018) purported that monoculture cropping may explain cases of low genetic diversity of Fusarium equiesti populations. However, Dinolfo et al (2017) also reported that geographic isolation, ecological conditions, and crop rotation systems may not have a significant effect on the genetic variability and distribution of F. poae isolates which may suggest pathosystemspecific interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The major Fusarium species that infect many foods and feed crops include F. oxysporum , F. culmorum, F. verticillioides, and F. proliferatum. F. oxysporum is one of the most critical soil-borne plant pathogens as it infects many crops and is responsible for massive crop losses [ 7 ]. F. culmorum is known to infest wheat worldwide, causing wheat blight and crown rot of cereals, resulting in detrimental losses of this economically important crop [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%